Effects of trade logistics on international trade: A systematic literature review - Yekini Ojenya Salawu; Seyed Mohammedreza Ghadiri; Mojeed Olayiwola Giwa (Cogent Business & Management, 2022)
There have been experiences of a declining interest in trade logistics and international trade research in the practitioners' communities. The body of research on its development appears fragmented owing to several and continuous progressive areas which covered many fields. From the transport and logistics management perspective, this systematic literature review (SLR) aims at ascertaining the focus of researches between 1999 and 2019 on some specific aspects of the current study as well as evaluating the methodologies adopted for such previous studies and how the future studies can benefit from it. The main facts emanating from SLR on trade logistics and economic development with the inclusive of a developing economy made up of 134 peered review articles discussed. The corpus ensuing from the review has been used to create a citation network study which underpins the recognition of the most investigated topics and their methodological approaches. The structural backbone that contributed to the rise of this investigation process ultimately in the field is pointed out, identified and has throws up areas of triggering interest for research opportunities. The results provide insights about the research path, current trends and future research directions in the field of trade logistics and international trade development.
Keywords: 650; international trade; systematic literature review; supply chain management; trade logistics; transport